Five new species of the genus Pholcus Walckenaer (Araneae: Pholcidae) from South Korea - Lee, Jun-Gi; Lee, Jun-Ho; Choi, Doo-Young; Park, Sun-Jae; Kim, A-Young; Kim, Sam-Kyu (Zootaxa, 2021)
Although the high level of species diversity within the Pholcus phungiformes-group (Araneae: Pholcidae) in the Korean Peninsula has been recognized recently, taxonomic studies, including new species discovery, have not been conducted in western regions of South Korea. In this study, five additional species belonging to the Pholcus phungiformes-group discovered from Seoul and surrounding areas are described as new, viz., Pholcus seoulensis Lee & Lee, sp. nov. Pholcus suraksanensis Lee & Lee, sp. nov., Pholcus incheonensis Lee & Lee, sp. nov., Pholcus seokmodoensis Lee & Lee, sp. nov. and Pholcus chilgapsanensis Lee & Lee, sp. nov. Detailed descriptions and geographic distributions are provided with accompanying photographs.